2018
DOI: 10.1259/bjr.20170956
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of suspected pulmonary embolism and deep venous thrombosis in obese patients

Abstract: Obesity is a growing problem around the world, and radiology departments frequently encounter difficulties related to large patient size. Diagnosis and management of suspected venous thromboembolism, in particular deep venous thrombosis (DVT) and pulmonary embolism (PE), are challenging even in some lean patients, and can become even more complicated in the setting of obesity. Many obstacles must be overcome to obtain imaging examinations in obese patients with suspected PE and/or DVT, and to ensure that these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 81 publications
0
18
0
1
Order By: Relevance
“…This technique is suited to CTPA because of its short scan duration, usually within four to six seconds, depending on Z-axis coverage. Therefore, to compensate for obese patients, increasing contrast administration rate and higher concentrations of iodinated contrast media may help maintain diagnostic PA enhancement levels [33,34]. This study highlights the importance of tailoring imaging techniques to individual patients; implementation of protocol B using a weight-adjusted contrast dose demonstrated a significant increase in PA enhancement in this cohort from 264.1 HU (protocol A) to 312.9 HU (protocol B), an increase of 18.48% (P ¼ X).…”
Section: Discussionmentioning
confidence: 99%
“…This technique is suited to CTPA because of its short scan duration, usually within four to six seconds, depending on Z-axis coverage. Therefore, to compensate for obese patients, increasing contrast administration rate and higher concentrations of iodinated contrast media may help maintain diagnostic PA enhancement levels [33,34]. This study highlights the importance of tailoring imaging techniques to individual patients; implementation of protocol B using a weight-adjusted contrast dose demonstrated a significant increase in PA enhancement in this cohort from 264.1 HU (protocol A) to 312.9 HU (protocol B), an increase of 18.48% (P ¼ X).…”
Section: Discussionmentioning
confidence: 99%
“…69 Diagnosis of VTE on ultrasound in obesity may be challenging because increased subcutaneous tissue can make visualizing deeper proximal veins difficult. 70 Establishing venous compressibility with significant subcutaneous tissue may be difficult, potentially resulting in false-positive results. 70 Physicians should incorporate a careful physical examination and clinical impression into the interpretation of ultrasound results in critically ill patients with obesity and suspected VTE.…”
Section: Thrombosismentioning
confidence: 99%
“…Slowing gantry rotation and lowering the pitch can also be helpful in reducing image noise, however these modifications come at a cost of increasing risk of motion artifact and increased radiation dose. 13 The use of iterative reconstruction in this patient population can be useful to improve image quality while minimizing radiation dose. 14…”
Section: Decreased Signal To Noisementioning
confidence: 99%
“…Although kVp can be increased as high as 140, multiple studies have shown that 120 kVp is adequate for most obese patients. 13 Increasing the mAs will also decrease noise, but at the cost of increasing radiation dose to the patient. The use of automatic tube current modulation software permits automatic adjustment of the tube current according to patient size and can help to optimize image quality without excess radiation exposure.…”
Section: Decreased Signal To Noisementioning
confidence: 99%
See 1 more Smart Citation